Identification and Characterization of the Seed Storage Proteins and Related Genes of Cannabis sativa L. - Sun, Xin; Sun, Yao; Li, Yao; Wu, Qiong; Wang, Lei (Frontiers in Nutrition, 2021)
Hemp (Cannabis sativa L.) seed is emerging as a novel source of plant protein owing to its rich protein content and reasonable nutritional structure. In the current study, the storage proteins of hemp seed were extracted using different methods. The modified Osborne method yielded maximum extraction of the hemp seed storage proteins, while degreasing had little effect on the hemp seed protein (HSP) extraction. Protein identification results revealed that 11S globulin (edestin) was the most abundant protein in hemp seed, and the molecular weights of the two subunits of this protein were approximately 35 kDa and 20 kDa, respectively. The second most abundant protein was 2S albumin (Cs2S), with a molecular weight of approximately 14-15 kDa. The least abundant protein was 7S vicilin-like protein (Cs7S), with a molecular weight of approximately 47 kDa. Subsequently, gene families encoding these three storage protein classes, including three genes for edestin, two for Cs2S, and one for Cs7S, were cloned and then analyzed for amino acid composition and structure. The three edestins were different in their amino acid sequences and calculated molecular weights. The analysis of coding sequences revealed a higher percentage of similarity (62.7%) between Edestin1 and Edestin3, while the similarity decreased significantly to approximately 57% between Edestin1 and Edestin2, and 58% between Edestin2 and Edestin3. The calculated protein molecular weight was the highest for the protein encoded by Edestin1 and the smallest for the protein encoded by Edestin2. All three edestins were rich in arginine, while Edestin3 had a higher methionine content relative to that in the other two, which proved that Edestin3 had a better nutritional value. Cs2S and Cs7S were different from those reported in previous studies. Therefore, it could be inferred that amino acid composition varies with different hemp cultivars. The current research brought significant theoretical advance in illuminating the understanding of hemp seed storage protein and would have significance for future research on improving the nutritional quality of hemp seed and developing bioactive peptides.